Potency of Jelly Extracts from Tamarillo Seeds (Solanum betaceae) on Diabetes Trough A-Glucosidase Enzyme Inhibition - Puspawati, GAK Diah; Ekawati, I Gusti Ayu; Ina, Putu Timur (Journal of Food Security and Agriculture, 2017)
Aim of the study was to determine potency of jelly extract pigment of tamarillo seeds on diabetes trough ?- glucosidase enzyme inhibition by in vitro assay. Preliminary research was conducted to obtain optimum enzyme substrate concentration, enzyme concentration, temperature, pH and duration of the enzyme incubation, followed by the main study using a completed randomized design. Treatments were divided into 6 groups: 1) control, acarbose 1%; 2) extract concentration of 0.0625%; 3) extract concentration of 0.125%; 4) extract concentration of 0.25%; 5) extract concentration of 0.50%, and 6) extract concentration of 1%. The results showed that the optimum enzyme substrate concentration, enzyme concentration, pH and temperature of enzyme incubation were on pH 6.8 and a temperature of 37°C for 15 minutes. The higher of enzyme substrate concentration was followed higher percentage of inhibition whereas IC50 on the enzyme glucosidase inhibition was 20.44 ug / ml.